The translation quality of speech acts on the label of product packaging - Setyowati, Lilis; Nababan, Mangatur (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
The translation of speech acts on product packaging labels was the object of this research. This study aimed to analyze the types of speech acts, translation techniques used by translators to translate label text, and to identify how these techniques affected changing speech acts on product packaging labels. A qualitative descriptive approach was used in this study. The data was presented in the form of utterances on packaging labels that included speech acts and their translations. Document analysis and focus group discussion were used to gather the data. According to the findings, the researcher discovered 94 different forms of speech acts. The translator used 14 different translation techniques in translating the label. Several translation techniques used in this study affect the changing of speech acts in the target language. Deletion, reduction, modulation, paraphrase, and compensation techniques were found to induce a change in speech acts. There were 12 data of the speech acts shifting. The cumulative score for the quality of the translation on the product packaging label was 2.75.